2010
DOI: 10.1074/mcp.m900260-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun Proteomics Analysis of Hibernating Arctic Ground Squirrels

Abstract: Mammalian hibernation involves complex mechanisms of metabolic reprogramming and tissue protection. Previous gene expression studies of hibernation have mainly focused on changes at the mRNA level. Large scale proteomics studies on hibernation have lagged behind largely because of the lack of an adequate protein database specific for hibernating species. We constructed a ground squirrel protein database for protein identification and used a label-free shotgun proteomics approach to analyze protein expression t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
89
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 45 publications
11
89
0
Order By: Relevance
“…For example, while the expression of collagen decreases during torpor, the expression of SMA shows a gradual increase. Changes in protein expression during torpor is in line with the previous finding that there is a substantial post-transcriptional regulation of proteins during torpor-arousal cycles of hibernation (Shao et al, 2010). It has also been shown that proteolysis is depressed during torpor (Velickovska et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…For example, while the expression of collagen decreases during torpor, the expression of SMA shows a gradual increase. Changes in protein expression during torpor is in line with the previous finding that there is a substantial post-transcriptional regulation of proteins during torpor-arousal cycles of hibernation (Shao et al, 2010). It has also been shown that proteolysis is depressed during torpor (Velickovska et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, transcripts for metabolic genes become rapidly depleted following arousal (Yan et al, 2008). Direct comparisons of mRNA and protein levels for the same gene correlate at best with r-values of 0.6 in hibernating arctic ground squirrels and genes and proteins show no correlation at all when comparing squirrels in late torpor and those in early arousal (r0.065) (Shao et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Talin1 overexpression enhances cancer cell adhesion, migration, and invasion by activating survival signals and conferring resistance to anoikis (Sakamoto et al, 2010). Other examples are adenylate cyclase-associated protein 1 and human fatty acid synthase (Yamazaki et al, 2009;Shao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%